The last one
Jfjjdjdjjdjfjjdjdjjdjxj
Answer: y = -3(x +
)² +
,
,
<u>Step-by-step explanation:</u>
First, you need to complete the square:
y = -3x² - 5x + 1
<u> -1 </u> <u> -1 </u>
y - 1 = -3x² - 5x
y - 1 = -3(x² + ![\frac{5}{3}x](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7Dx)
y - 1 + -3(
) = -3(x² +
+
)
↑ ↓ ↑
= ![(\frac{5}{3*2})^{2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B5%7D%7B3%2A2%7D%29%5E%7B2%7D)
y - 1 -
= -3(x +
)²
y -
-
= -3(x +
)²
y -
= -3(x +
)²
y = -3(x +
)² +
Now, it is in the form of y = a(x - h)² + k <em>where (h, k) is the vertex</em>
Vertex =
,
Answer:
8
Step-by-step explanation:
The domain is from the points (-4,0) through (4,0).